Full‐color Persistent Room‐temperature Phosphorescence from Carbon Dot Composites Based on a Single Nonaromatic Carbon Source. Issue 2 (13th December 2022) - Wang, Xiaolang; Wang, Shuaiqi; Huang, Yuanshan; Huang, Limei; Sun, Jianping; Lin, Zhenghuan
Abstract: Herein, a series of carbon dot composites (CDC) with full‐color and long‐lived room‐temperature phosphorescence (RTP) are prepared by a simple solid‐phase one‐step method from a single non‐conjugated and non‐aromatic carbon source. The RTP emission wavelength can be adjusted from 462 to 623 nm by changing the feeding ratio and reaction temperature. The luminescent lifetime and quantum yield of a green emissive CDC (AB‐CDC‐3) reach 1.1 s and 39%, respectively, because of the close interaction between carbon dots and inorganic matrix. Due to the existence of multiple luminescent centers, these CDC exhibit excitation wavelength‐dependent RTP and a white emission when excited at a specific wavelength. A single‐component afterglow luminescent diode based on AB‐CDC‐4 shows a high‐quality white emission with CIE of (0.30, 0.33) and color‐rendering index of 88. Based on the unique photophysical properties of the composites, they exhibit huge application potential in the field of multilevel anti‐counterfeiting, fingerprint identification, and optoelectronic devices. Abstract : Carbon dot composites (CDC) obtained by a green synthetic method from a single non‐aromatic carbon source show tunable afterglow and white emission with a CIE of (0.30, 0.33) and CRI of 88.